A severe case of pemphigoid gestationis persisting after labour - case report and review of the literature - Herman, Hynek; Krepelka, Petr; Faridova, Adela T.; Trojanova, Klara; Hanacek, Jiri; Jaluvkova, Barbora; Feyereisl, Jaroslav; Gkalpakiotis, Spyridon (Biomedical papers, 2024)
Background and Aim. Pemphigoid gestationis (PG) is a rare skin disease of pregnancy. Given its incidence in pregnant women, physicians and especially obstetricians may not encounter this diagnosis in their entire career. We find this to be a major problem and there is an obligation to report it in as much detail as possible along with recommended treatments with proven efficacy. Case report. We describe the case of a 27 year old patient who was referred to the dermatology department with severe dissemination of blisters in the 9th week of pregnancy. She was diagnosed with pemphigoid gestationis in her first pregnancy. High doses of corticosteroids were initiated but due to inadequate effect cyclosporine was added. The pregnancy was complicated with gestational diabetes. The patient gave birth in her 33rd week by caesarian section due to premature rupture of the membrane. Vesicles were seen on the newborn immediately after birth which diminished spontaneously over 2 weeks. Blisters were still seen on the patient 1 month after labor even with the combination of systemic corticosteroids with cyclosporine. Conclusion. PG is a rare dermatosis of pregnancy. The course of the disease can be severe, necessitating systemic therapy. As described in this patient, systemic corticosteroids may not be sufficient and adding another immunosuppressive treatment may be needed. If pemphigoid gestationis has occurred during a previous pregnancy it is advised to reconsider another pregnancy.
Keywords: pemphigoid gestationis; herpes gestationis; blisters; pregnancy